A retrospective review of ampicillin-sulbactam and amoxicillin + clavulanate vs cefazolin/cephalexin and erythromycin in the setting of preterm premature rupture of membranes: maternal and neonatal outcomes - Ehsanipoor, Robert M.; Chung, Judith H.; Clock, Charlotte A.; McNulty, Jennifer A.; Wing, Deborah A. (American journal of obstetrics and gynecology, 2008)
The purpose of this study was to compare the efficacy and outcomes of 2 different antibiotic regimens that are used to prolong latency in preterm premature rupture of membranes. The primary objective was to determine whether the use of ampicillin-sulbactam/amoxicillin + clavulanate was associated with an increased risk of necrotizing enterocolitis. A retrospective review of pregnancies that were complicated by preterm premature rupture of membranes from 1999-2006 at 2 institutions was performed. Outcomes were compared between subjects who received parenteral ampicillin-sulbactam followed by oral amoxicillin + clavulanate (protocol A) and subjects who received parenteral cefazolin and erythromycin followed by oral cephalexin and erythromycin (protocol B). There were 147 women who were evaluated; 88 women received protocol A, and 59 women received protocol B. There were no differences in latency period, gestational age at delivery, or route of delivery. The incidence of necrotizing enterocolitis was 8.0% and 10.2% for protocol A and protocol B, respectively ( P = .64). Ampicillin-sulbactam/amoxicillin + clavulanate was not associated with an increase in neonatal necrotizing enterocolitis. Erythromycin in combination with cefazolin and cephalexin is an effective latency antibiotic regimen.